En appel til erindringen. Kollektiv erindring og det infra-ordinære i Georges Perecs "Je me souviens" - Løkkegaard, Tue (Passage - Tidsskrift for litteratur og kritik, 2013)
Tue Løkkegaard: “An Appeal to Memory. Collective Memory and the Infra- Ordinary in Georges Perec’s Je me souviens” This article analyzes the book Je me souviens by French author Georges Perec. The book’s composition of 480 recollections associated with the everyday and the banal is investigated through Perec’s notion of the infra-ordinary and collective memory. Perec’s book and the everydayness are situated as a field of experience that consists of both an individual and a collective presence, thus enabling Je me souviens to act as a reminder and a visualization of both the potential and the processes of subjectivation situated in the unnoticed fabric of the everyday.